Implementing hybrid telerehabilitation following major cardiac surgery during COVID-19 pandemic in Hong Kong. (11th May 2022) - Wong, K F; Fu, N; Fan, KYY; Cheng, K Y; Wong, K L; Yung, C Y; Ho, C K L; Au, TWK
Abstract: Funding Acknowledgements: Type of funding sources: Public hospital(s). Main funding source(s): Department budget Background: Aerobic exercise is a critical component of cardiac rehabilitation (CR) for patients (pts) who have undergone cardiac surgery. Exercise-based CR is ideally home-based and directly supervised by a trained physiotherapist. During COVID-19 pandemic in Hong Kong, there was increasing emphasis on social distancing and caregiving strategies to better reach pts outside hospital. As most cardiac surgeries were performed on urgent clinical needs including heart transplantation and aortic dissection, we implemented hybrid telerehabilitation (HTR) with transition to the use of remote care in order to continue comprehensive CR. We report the functional outcome of HTR group compared with usual care (UC) group. Methods: From 7/2020 to10/2021, 36 pts ( 67% men, mean age 57±9.2 years) were enrolled into HTR (n=18) and UC (n=18) groups respectively for 12 weeks' duration. Demographics in both groups were similar. Types of cardiac surgeries were heart transplant (n=5; 14%), CABG (n=6;17%), valvular surgery (n=17; 47%) and aorta operation (n=8; 22%). An individualized exercise prescription for HTR at home was determined based on initial standardized assessments in hospital and tailored to fit lifestyle and home environment. For HTR group, the goal is set at 150 minutes of low to moderate-intensity aerobic exercise per week at home. Exercise is progressed weekly based on daily metrics recorded by wearable device (exercise log and % target heart rate reserve (THRR) attained) and rate of perceived exertion (RPE). These were reported by pts through an online survey after each exercise session which were reviewed daily, with progress follow-up by phone calls or text messages on a weekly basis. Functional capacity parameters were evaluated using symptom limited exercise treadmill test (ETT) and 6 minute walk test (6MWT). The advised level is based on the current activity level of the patient using a MET score list at intake by the physiotherapist. Handgrip and quadriceps strength were measured. Results: All pts participated the programs. Both groups demonstrated significant improvement in MET scores and 6MWT after completion of CR programs.(Table ) Average exercise time at home was reported to be 379 ±98 minutes/ week (72% achieved >150 minutes/ week). Compared with UC, HTR showed significantly increased % change in MET score at baseline and upon completion of CR (22.1% vs 7%; p=0.02) and 6MWT (11.1% vs 5.3%; p=0.01). The effect muscle strength were similar in both groups with improving trend but no significant % change at baseline and end of CR. Conclusion: Significant improvement in functional status can be demonstrated in comprehensive individualized HTR program in pts after major cardiac surgery. Adoption of digital technology with full integration into standard cardiac rehabilitation program should be recommended.